Dampak Penerapan Kebijakan Dosen Pada Program Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Gorontalo - Chalid Luneto; Yanti Aneta; Rustam Tohopi (Jayapangus Press, 2025)
This study aims to analyze the implementation of institutional policies in research and community service programs at Universitas Negeri Gorontalo and their impact on faculty participation and institutional development. The research employed a qualitative method with a case study approach through in-depth interviews, field observations, and document analysis during the 2020-2024 period. Findings reveal significant dynamics in faculty participation. The DRTPM/DIKTI research scheme experienced a surge from 15 activities (2020) to 59 activities (2024), reflecting positive adaptation to national policies. However, there is high dependency on the PNBP scheme which dominates 80.4% of research activities (1,448 out of 1,801 total) and 74.1% of community service activities (1,125 out of 1,519 total) over five years. Top-down policies proved to generate resistance and decreased faculty motivation, particularly among junior faculty and those with lower functional positions. Conversely, faculties with internal support systems such as proposal clinics successfully increased participation significantly. Output quality varies greatly among faculties, with faculties having review and mentoring systems producing better publications in accredited journals and international proceedings. The research conclusion confirms that successful program implementation is determined by participatory policy design, adequate administrative support, and collaborative academic culture. Strategic implications include the need for reformulation of evaluation systems based on output quality and sustainable institutional transformation to strengthen the institution's position in national higher education.